2011
DOI: 10.1097/aap.0b013e3182176f42
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Continuous Thoracic Epidural With Paravertebral Block on Perioperative Analgesia and Hemodynamic Stability in Patients Having Open Lung Surgery

Abstract: Under the conditions of our study, continuous paravertebral block resulted in similar analgesia but greater hemodynamic stability than epidural analgesia in patients having thoracotomy. Paravertebral block also required smaller volume of colloids and vasopressors to maintain the target oxygen delivery index (DO2I).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
73
0
7

Year Published

2013
2013
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 113 publications
(83 citation statements)
references
References 28 publications
3
73
0
7
Order By: Relevance
“…PV alana enjekte edilen anestezik ajan, interkostal sinirleri, dorsal kök-leri ve sempatik zinciri bloke edilerek yoğun duyusal ve sempatik blok geliştirmektedir. [2][3][4][5][6][7] Çalışmamıza benzer olarak, 10 randomize çalışmanın yer aldığı ve torakotomi sonrası ED ve PV analjezinin karşı-laştırıldığı bir meta-analizde (10 çalışmanın 4'ünde ED aralıktan ve birinde PV aralıktan lokal anestezik …”
Section: Discussionunclassified
See 3 more Smart Citations
“…PV alana enjekte edilen anestezik ajan, interkostal sinirleri, dorsal kök-leri ve sempatik zinciri bloke edilerek yoğun duyusal ve sempatik blok geliştirmektedir. [2][3][4][5][6][7] Çalışmamıza benzer olarak, 10 randomize çalışmanın yer aldığı ve torakotomi sonrası ED ve PV analjezinin karşı-laştırıldığı bir meta-analizde (10 çalışmanın 4'ünde ED aralıktan ve birinde PV aralıktan lokal anestezik …”
Section: Discussionunclassified
“…Çalışmamıza benzer olarak, paravertebral analjezide, lokal anesteziklerin somatik köklere yakın ve tek taraflı dağılımı sonucunda hipotansiyonun görülme sıklığının daha düşük olduğu bulunmuştur. [3][4][5][6][7][8] Torasik paravertebral anestezinin epidural anesteziden daha az intravenöz kolloid ve daha az vazopressör gerektirerek daha iyi perioperatif hemodinamik stabilite sağladığı bildirilmiştir. [2][3][4]7] Çalışmamızda, solunum sayısı paravertebral analjezi grubunda daha düşükse de istatistiksel olarak anlamlı bulunmamıştır.…”
Section: Pain a Riunclassified
See 2 more Smart Citations
“…As a result, paravertebral block applications are becoming increasingly common [8,9]. Some earlier studies have already reported that bupivacaine and levobupivacaine can provide sufficient analgesia in paravertebral block applications [10,11].…”
Section: Discussionmentioning
confidence: 99%